Utilization of Video Otoscopes for Otoscopy Skills Training of Third Year Medical Students - Cavuoto Petrizzo M; Olvet DM; Samuels R; Paul A; John JT; Pawelczak M; Steiner SD (Advances in Medical Education and Practice, 2023)
Marie Cavuoto Petrizzo,1 Doreen M Olvet,2 Roya Samuels,3 Aleena Paul,4 Janice T John,5 Melissa Pawelczak,1 Shara D Steiner6 1Departments of Science Education and Pediatrics, Zucker School of Medicine, Hempstead, NY, USA; 2Department of Science Education, Zucker School of Medicine, Hempstead, NY, USA; 3Department of Pediatrics, Zucker School of Medicine, Hempstead, NY, USA; 4Departments of Pediatrics and Family and Community Medicine, New York Medical College, Valhalla, NY, USA; 5Department of Pediatrics, Albert Einstein College of Medicine, Bronx, NY, USA; 6Specialized Programs in Education, Zucker School of Medicine, Hempstead, NY, USACorrespondence: Marie Cavuoto Petrizzo, Departments of Science Education and Pediatrics, Zucker School of Medicine, 500 Hofstra University, W227, Hempstead, NY, 11549, USA, Tel +1 516 463-7476, Fax +1 516.463.5631, Email Marie.C.Petrizzo@hofstra.eduPurpose: Effective teaching and assessment of otologic examinations are challenging. Current methods of teaching otoscopy using traditional otoscopes have significant limitations. We hypothesized that use of all-in-one video otoscopes provides students with an opportunity for real-time faculty feedback and re-practicing of skills, increasing self-reported confidence.Methods: An otoscopy microskills competency checklist was provided to third-year medical students during their pediatric clerkship to self-assess otoscopy technique during patient examinations, and to clinical preceptors to assess and provide feedback during exams. Over the course of two years, we collected data from students randomly assigned to train on a video otoscope or a traditional otoscope during the clerkship. Pre- and post-clerkship surveys measured confidence in performing otoscopy microskills, making a diagnosis and documentation of findings. For those students who trained on the video otoscope, we solicited post-clerkship feedback on the experience of using a video otoscope.Results: Pre-clerkship confidence did not differ between the groups, but the video otoscope trained group had significantly higher scores than the traditional otoscope trained group on all self-reported technical and diagnostic microskills confidence questions items post-clerkship. Students trained on video otoscopes had a significant increase in confidence with all microskills items (p-values< 0.001), however confidence in the traditional otoscope trained group did not change over time (p-values> 0.10). Qualitative feedback from the video otoscope trained group reflected positive experiences regarding “technique/positioning” and “feedback from preceptors.”.Conclusion: Teaching otoscopy skills to pediatric clerkship medical students using a video otoscope significantly enhanced confidence compared to those training on a traditional otoscope by 1. enabling preceptors and students to simultaneously visualize otoscopy findings 2. allowing preceptors to provide real-time feedback and 3. providing opportunity for deliberate practice of microskills. We encourage the use of video otoscopes to augment student confidence and self-efficacy when training in otoscopy.Keywords: medical students, technology, physical diagnosis, otoscopy